2015
DOI: 10.3233/ch-131727
|View full text |Cite
|
Sign up to set email alerts
|

Indirect viscosimetric method is less accurate than ektacytometry for the measurement of red blood cell deformability

Abstract: The aim of this study was to test the accuracy of viscosimetric method to estimate the red blood cell (RBC) deformability properties. Thirty-three subjects were enrolled in this study: 6 healthy subjects (AA), 11 patients with sickle cell-hemoglobin C disease (SC) and 16 patients with sickle cell anemia (SS). Two methods were used to assess RBC deformability: 1) indirect viscosimetric method and 2) ektacytometry. The indirect viscosimetric method was based on the Dintenfass equation where blood viscosity, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
3
10
0
1
Order By: Relevance
“…In accordance with the literature (Vent-Schmidt et al, 2015), blood viscosity measured at an adjusted haematocrit was higher in SS than in control (AA) samples at all shear rates ( Fig 1A). While P188 treatment did not significantly affect blood viscosity in AA, it decreased blood viscosity at the three lowest shear rates in SS.…”
Section: P188 Treatment Decreases Rbc Aggregation and Blood Viscositysupporting
confidence: 91%
“…In accordance with the literature (Vent-Schmidt et al, 2015), blood viscosity measured at an adjusted haematocrit was higher in SS than in control (AA) samples at all shear rates ( Fig 1A). While P188 treatment did not significantly affect blood viscosity in AA, it decreased blood viscosity at the three lowest shear rates in SS.…”
Section: P188 Treatment Decreases Rbc Aggregation and Blood Viscositysupporting
confidence: 91%
“…sDI RBC curves detect subpopulations of cells that exist within bulk samples of RBCs that a simple average cell deformability cannot detect. This average value of deformability could be gauged at the bulk scale through the use of ektacytometry, but examining single cell distributions could provide information on how specific subpopulations of RBCs may cause disease complications, for example, such as vaso‐occlusive crises in SCD. It has been previously shown that patients on HU therapy exhibit lower rigidity in the RBC membrane than of those patients not on HU, albeit still lower than normal controls .…”
Section: Discussionmentioning
confidence: 99%
“…When de-oxygenated, the sickling of RBCs causes a further rise in blood viscosity at all shear rates [8]. Plasma viscosity has also been shown to be slightly increased in SCA patients at steady state [19] likely due to the increased concentration of circulating fibrinogen and other acute phase reactant proteins.…”
Section: Hemorheological Profile In Scd At Steady Statementioning
confidence: 99%